Delusions of control in a case of schizophrenia coexisting with a large cerebellar arachnoid cyst - Ying-Ying Wu; Yu-Chih Shen (Tzu Chi Medical Journal)
Arachnoid cyst is a benign, congenital space-occupying brain lesion, which has been found in patients with schizophrenia. The association between arachnoid cyst and schizophrenia remains controversial, but the location of the arachnoid cyst may give rise to a specific symptom presentation in schizophrenia. We present a 31-year-old woman with an established diagnosis of schizophrenia coexisting with a large cerebellar arachnoid cyst who presented mainly with delusions of control. This cerebellar arachnoid cyst and schizophrenia may have been found together coincidentally or brain dysfunction due to this cerebellar arachnoid cyst may have caused or contributed to the appearance of psychotic symptoms. The patient had an unsteady gait accompanied by delusions of control, and she showed a poor response to high-dose olanzapine treatment, suggesting the arachnoid cyst was associated with her schizophrenic symptoms. The cyst was over the right posterior fossa with cerebellum compression, which may have caused abnormality in the cerebellar–parietal network resulting in her delusions of control. This case indicates that there might be relationships between cerebellar lesions, schizophrenia, and delusions of control.